Anaerobic Power among Able-bodied Individuals versus Disabled Persons during arm cranking and Its Relationship to Hand-Grip Strength - Al-Rahamneh, Harran (Jordan Journal of Pharmaceutical Sciences, 2020)
Aim: This study assessed Wingate test performance among disabled individuals compared to able-bodied. It also assessed the relationship between arm cranking anaerobic power and hand-grip strength. Methods: Fifteen able-bodied men (age, 21.5 ± 1.2 y; height, 178 ± 7 cm; body mass, 77.7 ± 10.5 kg) and 11 disabled men (age, 33.6 ± 8.5 y; height, 158 ± 27 cm; body mass, 88.3 ± 22.7 kg) volunteered to take part in the study. Able-bodied participants completed two Wingate exercise tests; one leg cycling and one arm cranking. Disabled persons completed only the arm cranking Wingate exercise test. Hand-grip strength was measured for both hands for both groups. Results: Wingate test peak (801 ± 131 W vs. 481 ± 117 W, respectively P < 0.001) and mean (613 ± 107 W vs. 346 ± 75 W, respectively P < 0.001) power output during leg cycling were significantly higher than arm cranking. Peak (481 ± 117 W vs. 410 ± 146 W, respectively P > 0.05) and mean (346 ± 75 W & 311 ± 111 W, respectively P > 0.05) power output of able-bodied participants during arm cranking Wingate test were higher than disabled persons. There was a significant relationship between peak and mean Wingate test power output during arm cranking and hand-grip strength for both hands (P < 0.01). Conclusion: Wingate test performance was greater during leg cycling compared to arm cranking and in able-bodied participants compared to disabled individuals during arm cranking. There was a significant relationship between hand-grip strength and Wingate test performance for both groups. These findings indicate differences between able-bodied and disabled individuals in Wingate test performance and reveal aspects of fitness to be improved in disabled individuals.